A review of the genus Kalanchoe (Crassulaceae subfam. Cotyledonoideae) in the Euro-Mediterranean area, with an annotated catalogue and identification key - Gallo, Lorenzo; Smith, Gideon F. (Phytotaxa, 2024)
The genus Kalanchoe (with Bryophyllum included in its synonymy) (Crassulaceae subfam. Cotyledonoideae) has a wide natural geographical distribution range that stretches from Madagascar to some islands in the Indian Ocean off the east coast of Africa, to most of sub-Saharan and northern North Africa, and to the Near, Middle, and Far East. However, several representatives of the genus have been spread across mild-climate and even temperate parts of the world well beyond their natural distribution ranges because of their medicinal uses and because they are cultivated for ornamental (both indoor and outdoor) horticultural purposes. In addition, a number of taxa have become notorious in invasions biology as a result of casual introductions that probably resulted from surplus horticultural material being irresponsibly discarded. In the Euro-Mediterranean region 13 Kalanchoe taxa have spread widely into the natural and built environment. In the present paper the nomenclature of the 13 variously naturalised taxa is updated and corrected, and their country-level presence and spread in the Euro-Mediterranean are recorded. An analytical key is provided to facilitate the identification of the taxa that have escaped from cultivation in the Euro-Mediterranean region. A list of taxa that are cultivated but that have not become weedy, nor naturalised or invasive in the study area is provided. Most of the kalanchoes recorded here is illustrated.